METHODOLOGY OF TEACHING THE NERUSIAN AUDIENCE TYPES OF INDEPENDENT WORK (PHRASEOLOGICAL ANTONYMY) ON THE PRACTICAL STUDY OF THE RUSSIAN LANGUAGE - Irbutaeva Nigora Dilshodovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes the different-structured phraseological antonyms, the study of phraseological antonymy by non-Russian students by philologists. Conclusions about the relation of words and phraseological units are formulated.